1991
DOI: 10.1063/1.460839
|View full text |Cite
|
Sign up to set email alerts
|

Mode-selective bond fission: Comparison between the photodissociation of HOD (0,0,1) and HOD (1,0,0)

Abstract: The 193 nm photodissociation of individual rotational levels of HOD molecules excited with one quantum of O–H or O–D stretching vibrational energy is described. Stimulated Raman excitation and coherent anti-Stokes Raman scattering are used to prepare and detect, respectively, the (0,0,1) (O–H stretch) or (1,0,0) (O–D stretch) vibrationally excited HOD. The OD and OH fragments are detected by laser-induced fluorescence. In the photodissociation of HOD (0,0,1), the yield of both fragments is enhanced [relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 32 publications
3
42
0
Order By: Relevance
“…This chemistry would involve the processes (C) and (CH31)2-+C2H6 + 1 2 , (D) These are exoergic by -140 and -520 kJ Imol, respectively, assuming a dimer binding energy of 12 kJ/mol. 41 Our experimental result of very "cold" rotational and vibrational distribution of the 12 product could be consistent with a fourcenter concerted reaction, such as that shown in reaction (D). Although ground state four-center exchange reactions are forbidden by the Woodward-Hoffmann rules, the excited electronic state reaction is allowed.…”
Section: Reaction Dynamicssupporting
confidence: 86%
“…This chemistry would involve the processes (C) and (CH31)2-+C2H6 + 1 2 , (D) These are exoergic by -140 and -520 kJ Imol, respectively, assuming a dimer binding energy of 12 kJ/mol. 41 Our experimental result of very "cold" rotational and vibrational distribution of the 12 product could be consistent with a fourcenter concerted reaction, such as that shown in reaction (D). Although ground state four-center exchange reactions are forbidden by the Woodward-Hoffmann rules, the excited electronic state reaction is allowed.…”
Section: Reaction Dynamicssupporting
confidence: 86%
“…One of the remarkable examples is a bond-selected photodissociation of HOD molecule. [5][6][7][8][9][10] Crim and co-workers showed that the photolysis of HOD in the 4 O-H band produces OD fragments with at least 15 times higher yield than OH fragments. 5,7 On the other hand, Rosenwaks and coworkers reported that HOD molecules in the 3 O-D vibrational state preferentially photodissociate through the OHϩD channel.…”
Section: Introductionmentioning
confidence: 99%
“…However, localizing excitation in the reaction coordinate, on a practical time scale, is difficult because of extensive intramolecular state mixing. Nevertheless, successful examples of selectivity have been achieved following excitation of localized ultraviolet ͑UV͒ chromophores, 1 photoisomerization, 2 site specific photolysis of haloalkanes, 3 and vibrational excitation in H 2 O, 4 -7 HOD, 8,9 and D 2 O. 10 The water and its isotopically substituted analogs are particularly suitable for photodissociation studies since they comprise several different vibrational modes.…”
Section: Introductionmentioning
confidence: 99%